Analisis Lirik Lagu “Nia Anak Surga” Karya Erwin Chan Menggunakan Pendekatan Mimetik - Beby Anjelika (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Literary work is an expression of the representation of the author's mind using language as a medium, where the human or author's feelings here are personal in the form of experiences, thoughts, feelings, ideas, enthusiasm and beliefs which are formed in a picture of life that can brings out the charm that uses language tools in written form. According to Teeuw (1988:23) in (Asria Fera Nurnazilia et al., 2022) literature comes from the root word "sas" (Sanskrit) which means to direct, teach, give guidance and instruction, while the suffix "tra" means tool, means. So, lexically, literature means a collection of tools for teaching, manuals or good teaching books, such as silpasastra (architectural manual), kamasastra (love manual). Literature is a form of representation of an author's thoughts. Literary works are an art that has a human element in it that involves feelings. This research uses a qualitative descriptive research method. The main data of this research is a literary work in the form of poetry in the form of the lyrics of the song "Nia Anak Surga" by Erwin Chan with research data in the form of words, quotes and sentences whose meanings are analyzed using a mimetic approach. Data collection techniques use documentary techniques. The data analysis technique uses content analysis techniques. The aim of this research is to describe the meaning and mimetic evidence contained in the song "Nia Anak Surga" by Erwin Chan seen from mimetic studies.